Analisis Nilai Tambah Agroindustri Lanting Ubi Kayu Di Kecamatan Pasir Penyu Kabupaten Indragiri Hulu Provinsi Riau - Ernawati; Adriansyah; Noviana Yana; Ardila Ria; Khairudin (CV Edujavare Publishing, 2024)
Agroindustry is the process of converting primary production raw materials into secondary, raw materials into food that is ready for consumption. The cassava lanting agro-industry was carried out in Kembang Harum Village, Pasir Penyu District, Indragiri Hulu Regency, This research uses the Survey method, the analysis method is carried out descriptively qualitative and quantitative. The research objective was to analyze the lanting production process and the added value of cassava lanting products. The results showed that the production process used several stages including: procurement of raw materials, peeling, cutting, boiling, smoothing, lanting molding, drying, frying, draining oil and packaging. In addition, the value-added analysis shows that the average amount of added value for lanting cassava received by entrepreneurs is Rp. 25,000/kg of raw material or the ratio of added value to the average output value of 33.33% per production process period. This value-added ratio is included in the medium added value because it is between 15-40%.